Determining the Accuracy of Patient-Specific Temporomandibular Joint Endoprostheses Using Nav gational Surgical Templates - Terletskyi Р. О.; Chepurnyi Ю. В.; Kopchak А. В. (Actual Dentistry, 2025)
Abstract. Total joint replacement is indicated for congenital developmental anomalies, hereditary craniofacial syndromes, post-traumatic defects, deformities, ankylosis, severe degenerative osteoarthritis, condylar hyperplasia, mandibular tumors extending to the temporomandibular joint (TMJ), significant condylar resorption, osteonecrosis, and other conditions. Advancements in computer-aided design and manufacturing (CAD/CAM) technologies have led to the widespread use of patient-specific endoprostheses designed to accommodate each patient’s unique craniofacial anatomy. Navigation surgical guides have recently been increasingly recommended to place patient-specific constructs, osteotomies, and bone fragment repositioning. These guides enhance surgical precision by providing clear reference points and directional guidance. Objective. This study assessed the accuracy of TMJ patient-specific endoprosthesis placement achieved during surgery using navigation surgical guides compared to preoperative computer-aided planning. Additionally, factors influencing the magnitude of observed discrepancies were analyzed. Results and Conclusions. A comparative analysis of preoperative planning and postoperative outcomes in patients with TMJ disorders and trauma who underwent total joint replacement with patient-specific constructs fabricated using a digital protocol and CAD/CAM technology revealed discrepancies in the condylar component position. The median mean deviation was 1.02 mm (IQR 0.78–1.47), with a maximum deviation of 2.42 mm (IQR 2.03–4.26). In the glenoid fossa region, deviations were significantly lower (p < 0.05), with a median of 0.65 mm (IQR 0.47–1.16) and a maximum of 1.79 mm (IQR 1.46–2.02). These deviations were biomechanically acceptable and did not affect the aesthetic outcomes of endoprosthesis placement. In no case did the condylar head extend beyond the glenoid fossa due to its spatial configuration. Overall, the findings confirm the high precision of TMJ endoprosthesis placement using CAD/CAM technology.